Polycystic ovarian syndrome is linked to increased oxidative stress in Omani women - Sulaiman MAH; Al-Farsi YM; Al-Khaduri MM; Saleh J; Waly MI (Dove Medical Press, 2018)
Maha AH Sulaiman,1 Yahya M Al-Farsi,1 Maha M Al-Khaduri,2 Jumana Saleh,3 Mostafa I Waly4,5 1Department of Family Medicine and Public Health, College of Medicine and Health Sciences, Sultan Qaboos University, Al-Khoudh, Sultanate of Oman; 2Department of Obstetrics and Gynecology, College of Medicine and Health Sciences, Sultan Qaboos University, Al-Khoudh, Sultanate of Oman; 3Department of Biochemistry, College of Medicine and Health Sciences, Sultan Qaboos University, Al-Khoudh, Sultanate of Oman; 4Department of Food Science and Nutrition, College of Agricultural and Marine Sciences, Sultan Qaboos University, Al-Khoudh, Sultanate of Oman; 5Nutrition Department, High Institute of Public Health, Alexandria, Egypt Purpose: Literature emerging from Western countries has reported increased levels of serum oxidative stress markers among polycystic ovarian syndrome (PCOS) women. In the Arab region, there is limited research about the association between oxidative stress and PCOS. This study aimed to compare sociodemographic and clinical characteristics, sex hormones, and oxidative stress indices between PCOS women and non-PCOS women and to investigate the correlation between oxidative stress biomarkers and sex hormones.Methods: This hospital-based case-control study was conducted among reproductive-aged women. The study included 51 women diagnosed with PCOS (as per Rotterdam 2003 criteria) and 45 control women who were not diagnosed with PCOS. Serum samples were collected to measure the mean levels of the following sex hormones: total testosterone, dehydroepiandrosterone sulfate, estradiol and progesterone, as well as to measure biomarkers of oxidative stress including glutathione peroxidase (GPx), glutathione reductase (GR), glutathione (GSH), and total antioxidant capacity (TAC).Results: PCOS women exhibited clinical characteristics including irregular menses, hirsutism, and acne compared to the control group (P≤0.05). Significant differences were observed in the waist-hip ratio of PCOS women compared to controls (P=0.004). GPx and GR activity levels appeared to be higher among PCOS women compared to controls; however, no statistically significant differences were observed between the two groups (P>0.05). PCOS women had lower GSH and TAC levels compared to controls with a statistically significant difference observed for GSH levels (P=0.006). Correlation analysis showed a significant negative correlation between estradiol and TAC in the total sample (r=-0.284, P=0.005).Conclusion: This study provides supportive evidence that oxidative stress might play a role in the pathogenesis of PCOS and, hence, oxidative stress parameters could be suggested as diagnostic markers for early diagnosis of high-risk groups. Also, the study provides supportive evidence that obesity and sex hormones, particularly estradiol, in PCOS may contribute to enhanced oxidative stress. Keywords: PCOS, oxidative stress, Oman, case-control, anthropometric, glutathione